Tolkāppiyam in English : translation, with the Tamil text, transliteration in the roman script, introduction, glossary, and illustrations - Tolkāppiyar (Publication (Institute of Asian Studies (Madras, India)) ;, 2000)
Prijevod stare tamilske gramatike